(untitled) (World Bulletin of Social Sciences, 2023)
The influence of ethnocultural processes on the lifestyle of mountain and submountain inhabitants of Vakhshivor, Surkhandarya region. Vakhshivor mountain and sub-mountain inhabitants of Surkhandarya region are known for their lifestyle and literature. In this article, the impact of ethnocultural processes on the lifestyle of Vakhshivor mountain and submountain inhabitants should be analyzed